High-performance trimethylamine gas sensors based on defect-engineering MOF-derived ZnO nanoclusters with tunable surface oxygen vacancies. Issue 48 (1st November 2022) - Yu, Shaoyuan; Dong, Jingshi; Wang, He; Li, Sirui; Zhu, Hang; Yang, Tianye
Abstract : DE MOF-derived ZnO nanoclusters with tunable surface oxygen vacancies are synthesized. Comprehensive characterization techniques and DFT calculations indicate that surface oxygen vacancies effectively promote the TMA sensing performance. Abstract : In this study, we have successfully fabricated high-performance trimethylamine (TMA) sensors. Defect-engineering (DE) strategy in which two organic ligands, i.e., dicarboxylate and tricarboxylate coordinated with Zn 2+ ions, simultaneously, was adopted to obtain MOF-derived ZnO nanoclusters with tunable surface oxygen vacancies after the annealing process. The coordinate competition is expected to introduce more coordinate unsaturated metal sites (CUSs) in MOF materials and thus introduce more oxygen vacancies in MOF-derived materials. Results of gas sensing tests indicate that the dual ligand sensor (DL4) exhibits optimal TMA sensing performance including a high response value of 270.1, excellent selectivity, and good stability to 20 ppm TMA at a low operating temperature of 140 °C. Results of comprehensive characterization experiments including XPS, UV-vis spectra, PL spectra, and EPR indicate that the extraordinary TMA-sensing performance of the sensor can be attributed to abundant doubly positive oxygen vacancies on the ZnO nanocluster surface. The first-principles calculations including the TMA adsorption energy of the ZnO surface and the corresponding differential charge density were calculated using the software VASP (Vienna Ab initio Simulation Package), which further proved that the surface oxygen vacancy is beneficial to TMA sensing performance improvement. Furthermore, the TMA sensing mechanism is also discussed. The DE MOF-derived preparation strategy is a facile and effective method for designing high-performance metal oxide semiconductor gas sensing materials with tunable surface oxygen vacancies.